Cotinine-assessed second-hand smoke exposure and risk of cardiovascular disease in older adults. Issue 11 (17th May 2010) - Jefferis, B J; Lawlor, D A; Ebrahim, S; Wannamethee, S G; Feyerabend, C; Doig, M; McMeekin, L; Cook, D G; Whincup, P H
Abstract : Objectives: To examine whether second-hand smoke (SHS) exposure measured by serum cotinine is associated with increased coronary heart disease (CHD) and stroke risk among contemporary older British adults. Design: Prospective population-based study with self-reported medical history and health behaviours. Fasting blood samples were analysed for serum cotinine and cardiovascular disease (CVD) risk markers. Setting: Primary care centres in 25 British towns in 1998–2001. Patients: 8512 60–79-year-old men and women selected from primary care registers. Main outcome measures: Fatal and non-fatal myocardial infarction (MI; n=445) and stroke (n=386) during median 7.8-year follow-up. Main exposure: Observational study of serum cotinine assayed from fasting blood sample using liquid chromatography tandem mass spectrometry method, and self-reported smoking history. Results: Among 5374 non-smokers without pre-existing CVD, geometric mean cotinine was 0.15 ng/ml (IQR 0.05–0.30). Compared with non-smokers with cotinine ≤0.05 ng/ml, higher cotinine levels (0.06–0.19, 0.2–0.7 and 0.71–15.0 ng/ml) showed little association with MI; adjusted HRs were 0.92 (95% CI 0.63 to 1.35), 1.07 (0.73 to 1.55) and 1.09 (0.69 to 1.72), p(trend)=0.69. Equivalent HRs for stroke were 0.82 (0.55 to 1.23), 0.74 (0.48 to 1.13) and 0.69 (0.41 to 1.17), p(trend)=0.065. The adjustment for sociodemographic, behavioural and CVD risk factors had little effect on the results. The HR of MI for smokers (1–9 cigarettes/day) compared with non-smokers with cotinine ≤0.05 ng/ml was 2.14 (1.39 to 3.52) and 1.03 (0.52 to 2.04) for stroke. Conclusions: In contemporary older men and women, SHS exposure (predominantly at low levels) was not related to CHD or stroke risks, but we cannot rule out the possibility of modest effects at higher exposure levels.